Substratum interactions determine immune response to allogeneic transplants of endothelial cells - Wilcox, Elise C.; Edelman, Elazer R. (Frontiers in Immunology, 2022)
Endothelial cells (ECs) are central to vascular health but also interact with and regulate the immune system. Changes in endothelial state enable immune cells to migrate into the tissue to facilitate repair and fight infection. ECs modulate the function of immune cells through the expression of adhesion molecules, chemokines, major histocompatibility complex (MHC), and an array of co-stimulatory and inhibitor molecules. These interactions allow ECs to act as antigen presenting cells (APCs) and influence the outcome of immune recognition. This study elucidates how EC microenvironment, vascular cell biology, and immune response are not only connected but interdependent. More specifically, we explored how cell-substratum interactions influence EC antigen presentation and co-stimulation, and how these differences affect allorecognition in animal models of cell transplantation. Investigation of EC state was carried out using RNA sequencing while assessment of the allogeneic response includes measurements of immune cell cytotoxic ability, T cell proliferation, cytokine release, serum antibodies, and histological staining. Differences in substratum led to divergent EC phenotypes which in turn influenced immune response to transplanted cells, both due to the physical barrier of matrix-adhesion and differences in expression of surface markers. ECs grown in 2D on tissue culture plastic or in 3D on collagen scaffolds had significantly different basal levels of MHC expression, co-stimulatory and adhesion molecules. When treated with cytokines to mimic an inflammatory state, ECs did not converge to a single phenotype but rather responded differently based on their substratum. Generally, 3D ECs were more responsive to inflammatory stimuli than 2D ECs. These unique expression patterns measured in vitro also influence immune recognition in vivo. ECs grown in 2D were more likely to provoke a cytotoxic response while 3D ECs induced T cell proliferation. ECs are uniquely configured to sense not only local flow and mechanical forces but a range of markers related to systemic state, including immune function. ECs interact with immune cells with differing results depending on the environment in which the EC-lymphocyte interaction occurs. Therefore, understanding this relationship is essential to predicting and modifying the outcome of EC-immune interacts. We specifically examined the relationship between EC substratum and allorecognition.